Differential diagnosis of a swine epizootic of unknown etiology in Ibadan, Oyo State, Nigeria (2003)
Outbreaks of unconfirmed infections associated with high mortalities in pig herds were reported at the University of Ibadan Teaching and Research Farm, and in other parts of Ibadan, Nigeria between June and October 2001. Based on a tentative diagnosis of African Swine Fever and differential diagnosis of classical swine fever, encephalomyocarditis virus and anthrax, research was initiated between July and November 2001 to confirm the cause of the outbreak. This included farm visits to observe clinical signs, collect samples and do necropsies, electronic mail communication of presenting signs, Internet web searches, laboratory tests and serological (immunoblotting assay) tests. A confirmatory diagnosis of the infection as African Swine Fever (ASF) was reached. This diagnosis is important to enable researchers and appropriate authorities to introduce monitoring and control measures.